Are workers from waste sorting industry really protected by wearing filtering respiratory protective devices? The gap between the myth and reality - Viegas, Carla (2019)
One of the solutions for decreasing the workers' exposure to bioburden is the use of Filtering Respiratory Protective Devices (FRPD). As such it is important to determine whether these devices are fulfilling their protective role. This is the basis of the current study, aimed at characterizing bioburden retained by 120 FRPD (both in interior layers and in exhalation valves) through culture based-methods and molecular tools and also via analysis of antifungal resistance and mycotoxins profile. Our results show that Gram–Bacteria are present at a higher prevalence than total bacteria in both matrixes. Regarding fungal identification, Chrysonilia sitophila presented the highest prevalence on interior layers (55.1% on malt extract agar (MEA) supplemented with chloramphenicol (0.05%); 59.6% on dichloran-glycerol agar (DG18)), whereas on exhalation valves Aspergillus sp. presented the highest prevalence on MEA (6.8%) and C. sitophila on DG18 (36.3%). Among Aspergillus genera, section Fumigati was the one with the highest prevalence in both matrices. Aspergillus sp. was the most prevalent on exhalation valves (75.0% ITRA) in the screening of azole resistance. Fumigati section was the most abundant Aspergillus sp. detected on the interior layers (33.33%, 40 samples out of 120) and on the exhalation valves (1.66%, 2 samples out of 120). The interior layers and exhalation valves from workers with more waste contact showed an increased exposure to bioburden. This study showed that FRPD can have high levels of bioburden, toxigenic fungal strains and Aspergillus sections with reduced susceptibility to the tested azoles and can be used as a passive sampling method since it mimics the results obtained by active methods in previous studies. The gathered information will be useful to prioritize multiple interventions on workers’ education or even on FRPD replacement frequency.